PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 67 PEKANBARU - Rifani, Khalisa; Alpusari, Mahmud; Lazim. N, Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by teachers who are still using old method in teaching. Especially in science, generally teachers only teach without doing an experiment.Inquiry learning model is expected to improve students’ achievement in learning. This research used quasi experimental method with nonequivalent control group design.The purposes of Inquiry learning model are to know the effect of Inquiry learning model application in the experimental class and to know the difference of improvement in students' science achievement between experimental class and control class.This research was conducted in SD Negeri 67 Pekanbaru with class IV A as experiment class and class IV B as control class.From the research’s result showed that there is influence of Inquiry learning model in experiment class and there is difference of improvement students’ science achievementbetween experiment class and control class.In experimental class there was an increase in students’ achievement with an average gain of 0.68 in medium category. While in control class,students’ achievement increasing with an average gain of 0.42 in medium category.In this research, there is influence of Inquiry learning model to students’ achievement of experiment class with value (r) equal to 0,66 in strong relation category. Based on the coefficient of determination is 43%, means the application of inquiry learning model influencingexperimental class by 43% and 57% influenced by other factors. Thus, the Inquiri learning model affecting students' science achievement with a betterimprovement of students’ achievement than the application of lecturing methods.Key Words: Inkuiri, Science Achivements